Azathioprine as an adjuvant therapy in severe Graves’ disease: a randomized controlled open-label clinical trial - Allam, Magdy Mohamed; El-Zawawy, Hanaa Tarek; Kader Okda, Amr Abdel; Ali Alshaikh, Ayoub; Ghazy, Ramy Mohamed (Frontiers in Endocrinology, 2023)
Antithyroid drugs (ATD) are the first-line treatment for Graves’ disease (GD). We conducted a prospective, randomised, open-label, ¶llel-group clinical trial to study the effect of AZA as an adjuvant therapy on the efficacy of ATD in moderate and severe GD. The newly diagnosed, untreated, hyperthyroid patients with severe GD were recruited & randomised into 3 groups; into 3 groups; all of them received 45 mg carbimazole ( CM “starting dose” + propranolol 40- 120 mg daily. The first group (AZA1) received in addition 1 mg/kg/day AZA, the second group (AZA2) received in addition 2 mg/kg/day AZA, and the third group (control group) only received CM + propranolol. Thyroid stimulating hormone (TSH) & TSH receptor antibody (TRAb) were performed at baseline and every 3 months, FT3 & FT4 were performed at diagnosis, 1 month after the start of therapy, and every 3 months till 2 year after remission. Thyroid volume was assessed by ultrasound at baseline, and 1year after remission. By the end of follow‐up, there was a tendency for a higher remission rate in the AZA1 & AZA2 Vs controls (87.5% & 87.5% vs. 33.4 %, p =0.002). All over the course of follow-up, FT3, FT4, TSH, and TRAb were significantly different between AZA groups & control group, however no significant difference regarding thyroid volume. The descent in the concentrations of FT4, FT3, and TRAb were significantly faster in the AZA2 Vs AZA1. Relapse rate during the 12-month follow-up, insignificantly higher in control group versus either in the AZA1 or AZA2 group (10%, 4.4%, 4.4%, p = 0.05; respectively). The median relapse time was 18 months for the control group Vs 24 months for the AZA1 and AZA2 groups. The incremental cost-effectiveness ratio for AZA group compared to conventional group was 27,220.4EGP per remission reduction for patients using AZA as adjuvant for ATD. To summarize; AZA as an adjuvant treatment to the standard ATD therapy could be a novel, affordable, cost effective, and safe approach offering hope for patients with GD to achieve early and long-lasting medical remission.